Digital Financing Innovations and Their Impact on the Financial Performance of SMEs in the Digital Economy Era - Evangelina Balboa; Marlon Ladesma; Atty. Nicolai Manguerra (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This article delves into the transformative landscape of digital financing innovations and their impact on the financial performance of Small and Medium-sized Enterprises (SMEs) within the context of the digital economy era. Through a comprehensive exploration of literature and analysis of future trends, this study sheds light on the evolving dynamics of digital finance and its implications for SMEs. Key findings reveal a paradigm shift fueled by emerging technologies, including blockchain, artificial intelligence, and the Internet of Things. These technologies have ushered in a new era of financial inclusion, efficiency, and transparency, empowering SMEs with unprecedented access to affordable and tailored financial services. Furthermore, the research underscores the pivotal role of FinTech in driving innovation and disruption in the financial landscape. From integrated financial platforms to decentralized finance protocols, SMEs are presented with a myriad of digital solutions tailored to their unique needs, fostering resilience and competitiveness in an increasingly digitalized marketplace. Amidst these advancements, policymakers and regulatory authorities play a crucial role in shaping the digital finance ecosystem. Initiatives such as regulatory sandboxes and interoperable standards are essential to promote trust, stability, and consumer protection, ensuring that SMEs can fully harness the potential of digital financing to fuel economic growth and prosperity. In conclusion, this study highlights the immense promise of digital financing for SMEs in navigating the complexities of the digital economy era. By embracing digital innovation and fostering collaboration between stakeholders, SMEs can unlock new avenues for growth, enhance their competitiveness, and contribute to inclusive and sustainable economic development.